Can there be a Market for Cheap-Talk Information? An Experimental Investigation - Antonio Cabrales; Francesco Feri; Piero Gottardi; Miguel A. Meléndez-Jiménez (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper reports on experiments testing the viability of markets for cheap talk information. We find that the poor quality of the information transmitted leads to a collapse of information markets. The reasons for this are surprising given the previous experimental results on cheap-talk games. Our subjects provide low-quality information even when doing so does not increase their monetary payoff.
Keywords: D83; C72; G14; 330; experiment; cheap talk; auction; information acquisition; information sale